Função afim: uma proposta didática para o ensino médio usando o geogebra no contexto do trabalhador da cerâmica no Município de Russas - CE - Ferreira, Ronaldo Matoso (2021)
This work proposes to present a suggestion of a didactic sequence that aims to promote the articulation between the everyday life of students to mathematical concepts. The motivational reason for this research object emerged from the results of the external evaluation of the Permanent Evaluation System of the State of Ceará – SPAECE, which classifies the D28 as critical, by revealing the students' deficit in understanding and representing graphical and algebraic characteristics of the affine function. In that regard, the proposal becomes an alternative didactic support that tends to value the sociocultural and economic knowledge of the students through ethnomathematics trends and the use of technological resources. Based on this context, this research has the overall goal: subsidize teaching practice with the suggestion of a didactic sequence which involves the context of ceramics proposing activities carried out in the GeoGebra software. That said, the methodology used is qualitative and bibliographical. We support the discussions in the Common National Curriculum Base (2018), Brousseau (2008), Fani (2020), Luckesi (2018), Pippolo (2010), Vidal (2015), among others that contributed to the construction of the didactic proposal integrated to the conjuncture of the aforementioned context of the municipality of Russas/CE, because we think it is important to promote the encounter between mathematics and practical life, with a view to solving discourses based on which mathematics is not useful or is completely unknowable. As a result of this dissertation study, in addition to the didactic sequence mentioned, we present discussions inherent to the proposal's fundamentals